Differentiation of entomopathogenic fungus Beauveria bassiana (Ascomycetes: Hypocreales) isolates by PCR-RFLP - Sabbahi, Rachid; Lavallée, Robert; Merzouki, Abderrazzak; Guertin, Claude (Phytoprotection, 2009)
The entomopathogenic fungus Beauveria bassiana is a promising biological control agent of several insect pests in agriculture. Molecular approaches (PCR, DNA sequence analysis and PCR-RFLP) were used in our research as tools for the identification of different B. bassiana isolates. Our work consisted in identifying the 18S, ITS1, 5.8S, ITS2 and 28S regions of B. bassiana ribosomal DNA. The DNA sequences of the amplified regions showed that the 18S rDNA is the most conserved unit, with a high homology (99.5%) between the isolates studied, while the 3’ end of the 28S rDNA has a great variability, which makes it possible to differentiate the isolates. The PCR-RFLP method was used to monitor isolates of B. bassiana and distinguish them in a target pest, Lygus lineolaris. This method involved two main steps. First, PCR was used to amplify a region of the 28S gene of B. bassiana. Second, this PCR product was digested using restriction endonucleases, and the fragments produced were compared using gel electrophoresis. Because of the high specificity and sensitivity of PCR-RFLP, it was possible to discriminate between B. bassiana isolates using spores scraped from the surface of an infected insect as samples.